Effect of auxin and cytokinin on growth and galantamine production from in vitro shoot cultures of Narcissus tazetta var. chinensis - Seo, Hyewon; Lim, Jinsu; Nguyen, Bao Van; Uddin, Md Romij; Park, Chanung; Kwon, Do Yeon; Park, Sang Un (Journal of Phytology, 2025)
In recent years, in vitro plant culture techniques have significantly contributed to the large-scale propagation of plants and the production of bioactive compounds. This study investigates the impact of various plant growth regulators, including auxins (IAA, IBA, and NAA) and cytokinins (BAP, Kinetin, and TDZ), on the growth and galantamine production in shoot cultures of Narcissus tazetta var. chinensis cv. ‘Geumjanogdae’. One-year-old N. tazetta bulbs, which had been grown in a greenhouse, were used to regenerate shoots and establish in vitro cultures. The bulbs were zoomed in (2-3 bulbs were associated together in a flowering phase) exposed to a sterile environment and explants grew on Murashige and Skoog (MS) medium with different concentration of auxins and cytokinins. The objective of the study was to optimize simultaneous shoot growth and galantamine, a pharmacologically active alkaloid with great therapeutic significance as an Alzheimer disease medication, biosynthesis conditions. The culture with fresh weight and the galantamine content from the results showed significant effects of hormone treatments. Among the auxins, 2 mg/L NAA resulted in a maximum of 14.03 g/flask of fresh weight, and 1 mg/L IBA gave the best galantamine content of 277.64 μg/g dry weight (DW), respectively. The highest fresh weight of plant was in TDZ 2 mg/L with 16.33 g/flask, while it had the lowest rank in BAP 4 mg/L. Cytokinin, especially BAP, perform a significant role on galantamine enhancement synthesis by shoot cultures. The treatment BAP 4 mg/L had the highest galantamine content (232.16 μg/g DW) than that of TDZ and Kinetin. The study proved that the use of auxins and cytokinins could be manipulated in a way that not only improved shoot growth but also considerably increased the level of bioactive compounds like galantamine. This study also provides a clearer insight for optimal in vitro culture conditions by showing the performance of growth regulators on N. tazetta, which can serve as result of the basic information for large scale production of galantamine for medicinal purposes. Moreover, this work serves as an initial step towards the subsequent optimization of other bioactive compounds in different plant species.